MORFOMETRI BELANGKAS Tachypleus gigas (Muller, 1785) DI KAWASAN PESISIR BATU AMPAR, KALIMANTAN BARAT - Syahir, Sutan; Yanti, Ari Hepi; Setyawati, Tri Rima (Universitas Tanjungpura, 2020)
Tachypleus gigas is a species of horseshoe crab in Asia including Indonesia. Tachypleus gigas has a variety of morphological and morphometric forms in each different geographical area. The research aims to determine the morphological characteristics and the relationship of variation of T. gigas individual males and females consisting of the total length, carapace length, prosoma width and weight in a population. The results of the Independent Sample T-test of male and female crab t-test obtained tcount > t table shows that the T. gigas morphometry has a significant difference between male and female individuals. The horseshoe crab morphometry found in the Batu Ampar Coastal Area has an average size of a male individual with a width of prosoma 17.10±1.58 cm; total length of 36.01 ± 2.22 cm; carapace length 17.92 ± 1.56 cm and weight of 282.93 ± 49.89 g. Whereas female individual fruit has an average width of prosoma of 21.39 ± 2.97 cm; total length of 42.44 ± 3.82 cm; carapace length 23.90 ± 2.38 cm and weight of 662.69 ± 116.4 g. Variations in the morphometry relationships of Tachypleus gigas in Batu Ampar Coastal region indicate that the female individuals are greater than the male.